2007
DOI: 10.1021/op7001326
|View full text |Cite
|
Sign up to set email alerts
|

A Scaleable Synthesis of Methyl 3-Amino-5-(4-fluorobenzyl)-2-pyridinecarboxylate

Abstract: A scaleable synthesis of methyl 3-amino-5-(4-fluorobenzyl)-2pyridinecarboxylate (1b), starting from 5-bromo-2-methoxypyridine (8) and 4-fluorobenzaldehyde (9), is described. Key steps in the process include lithium-bromine exchange of 8, addition of the resulting lithiate to aldehyde 9, regioselective nitration of pyridone 12, and Pd-catalyzed alkoxycarbonylation of bromopyridine 15b. Overall yield of the five-stage synthesis was 23%; intermediates 10, 12, 13, 15b, and final product 1b • HCl were isolated as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Alternatively, it was found that the electron deficient 2-bromoquinoline was an excellent partner for cross-coupling with Pd(0) where carbonylation was achieved yielding the methyl ester 11 . 58 Subsequent saponification provided the requisite acid 7c , which led to the desired 4-CF 3 -quinox 8c . An alternative method was utilized to obtain the 4-chloro-quinox derivative 8d .…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, it was found that the electron deficient 2-bromoquinoline was an excellent partner for cross-coupling with Pd(0) where carbonylation was achieved yielding the methyl ester 11 . 58 Subsequent saponification provided the requisite acid 7c , which led to the desired 4-CF 3 -quinox 8c . An alternative method was utilized to obtain the 4-chloro-quinox derivative 8d .…”
Section: Resultsmentioning
confidence: 99%
“…This compound was first treated with n -BuLi in anhydrous diethyl ether at −50° C, followed by the addition of 2,6-difluorobenzaldehyde, 12 which afforded the alcohol 3 in 90% yield (Scheme 1). In the next step, deoxygenation of the benzylic hydroxyl group and deprotection of the methoxy group was achieved with trimethylsilyl iodide (generated in situ from TMSCl and NaI), trifluoroacetic acid (TFA) and triethylsilane (TES) 12,13 to give the pyridinone 4 in 88% yield. The reagents used in this step were in excess to ensure completion of both alterations in the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The 6-substituted 2(1H)-pyridones were synthesized starting with a Sonogashira coupling [37] between 6-bromo-2-methoxypyridine 5 and the corresponding terminal alkyne (6-8), obtaining 2-methoxypyridines (9-11) in good yields. The 6-substituted 2(1H)-pyridone receptors (12)(13)(14) were obtained in modest yields by adding TMSCl and dry NaI at room temperature in dry acetonitrile (Scheme 1) [38,39].…”
Section: Synthesismentioning
confidence: 99%